EFFECT OF INCOME ON THE NUTRITIONAL STATUS OF PRESCHOOLRS OF NAGPUR DISTRICT OF MAHARASHTRA STATE - Dr Saroj Bishnoi and Dr Deepali S. Kotwal, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The effects of nutrition on growth of pre-schoolers by socioeconomic status are not well known. This study aimed to examine the effects of dietary intake on growth outcomes in pre-schoolers by income level